STRATEGI LEMBAGA PENGELOLA HUTAN ADAT DALAM PENGEMBANGAN EKOWISATA DI HUTAN ADAT IMBO PUTUI KENEGERIAN PETAPAHAN KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2020-2023 - Putri, Shafiqa Hanisra; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Ecotourism development in Customary Forests can be said to be going well if the supporting factors for ecotourism development have been implemented, infrastructure development has been good, and indigenous peoples living around customary forests have been able to get results from ecotourism development. This research aims to find out the strategies carried out by the Traditional Forest Management Institution in realizing ecotourism development in the Imbo Putui Traditional Forest in 2020-2023 and to find out the obstacles faced by the Traditional Forest Management Institution in carrying out ecotourism development. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary data in the form of data obtained from related documents. Then the location of this research was in the Imbo Putui Kenegerian Petapahan Traditional Forest, Tapung District, Kampar Regency. This research found that the strategy carried out by the Traditional Forest Management Institute consisted of 5 factors, namely strengthening the concept of ecotourism, encouraging linkage of actors, encouraging participation and empowerment of the country's traditional tourism community, encouraging strategic units and carrying out promotions on various social media platforms. There are 3 factors regarding the existing obstacles to the development of ecotourism in the Imbo Putui Traditional Forest, namely the low commitment of the regional government of Kampar Regency and the village government in Kenegerian Petapahan, lack of facilities and infrastructure and inadequate accessibility. The author concludes that strengthening the concept of ecotourism is the most dominant and influential in realizing the strategy for developing ecotourism in the Imbo Putui Traditional Forest. This effort has included a main focus on developing ecotourism in biodiversity, implementing custom-based ecotourism and education as well as carrying out river rehabilitation so that sustainable ecotourism is maintained. and does not damage the environment. The most dominant obstacle is the low level of commitment of the regional government and village government in Kenegerian Petapahan because if there is no coordination between these actors, the development of ecotourism in the Imbo Putui Traditional Forest is hampered. Keywords: Ecotourism, Customary Forests, Customary Forest Management Institutions